Pemanfaatan Lahan Pekarangan dalam Mendukung Ketahanan Pangan Rumah Tangga di Desa Sumberjo Kabupaten Polewali Mandar - Helda H.; Mauliadi Ramli (Rayhan Intermedia, 2023)
This study aims to find out how residents use their yards in Sumberjo Village, Wonomulyo District, Polewali Mandar Regency, how residents use plant products from using their yards, as well as the implications of using yards for households. This study uses qualitative data and is descriptive in nature. The data collection technique was carried out using observation, interview, and documentation methods involving as many as 6 informants. The results of this study indicate that: (1) Land use in the form of yards has the potential to increase income. In addition, the yard land that has been utilized has a very high economic value after being properly utilized, so that it can help the family economy. (2) One form of land use is the cultivation of various types of vegetables in Sumberjo Village, Wonomulyo District, Polewali Mandar Regency. With food crops grown by residents in every household in Sumberjo Village, these food crops can help reduce budget expenses for daily needs. (3) Utilization of yards can provide opportunities for people in Sumberjo Village, Wonomulyo District, Polewali Mandar Regency, who have quite large yards. Besides being able to increase income, it can also make the yard have high economic value.